(untitled) (Al-Academy, 2023)
The formal diversity in designs is achieved by creating shapes and lines with a distinct movement pattern, which are preceded by mental processes. The greatest source of diversity in design in general and industrial design in particular is the creation of multiple directions for the completion of designs and the diversification of intellectual proposals for the design idea. The human activity that takes place around us in various fields of life takes place due to the diversity of movement in the form of the design product and its effectiveness through the dynamic diversity in the form, which differs in the methods of designing and showing it. He invents material value as a distinct artistic product that he owns A specific form or system that serves the recipient and is influenced by the control of the composition of the product to shape its shape and achieve the functional and aesthetic purpose in its construction in order to highlight the expressive ideas that the “designer” would like to communicate to the recipient. Thus, the first chapter included the question of the problem in the following question: What is the effect of kinetic diversity on the formal variables of the industrial product?Depending on its limits: Objectively: kinetic diversity and its effectiveness in the formal variables of industrial product design spatially: the Internet and temporally: 2010-2020. On the theoretical framework and previous studies according to the following division: The first topic included: the concept of movement and movement diversity and its effectiveness in design. The second topic included: dynamic diversity and its relationship to the external appearance of the industrial product. Then finish with the theoretical framework indicators.The third chapter contained the procedures, including: The research community, which is a group of industrial products with diverse motor performance in the design of the external shape, as it was determined in (20) models deliberately selected through the Internet for the period between (2010-2020) due to its suitability to achieve the goal of the research. The research sample included industrial products with motor performance of the formal variable, for which (2) samples were chosen from the comprehensiveness of the research community. He devoted his approach to the descriptive analytical approach for the purpose of obtaining valid results.The researcher analyzed his samples and summarized a number of results and conclusions, including: The formal variable of the kinetic design pattern came in a different way than the traditional designs, as in Model No. (1), as well as employing modern mechanical elements for the formal variables, especially Model No. (2).2. The formal vocabulary in the design of the product was determined by the ease of changes in form and function, within the determinants of the formal organization of the product, as in model (1,2), as it is considered a preliminary foundation for the effectiveness of constructive relations in the general formation of the kinetic system of the product’s shape.